2014
DOI: 10.1089/jwh.2013.4387
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Violence Against Women Act in Addressing Intimate Partner Violence: A Public Health Issue

Abstract: Intimate partner violence (IPV) is defined as violence committed by a current or former boyfriend or girlfriend, spouse or ex-spouse. Each year, 1.3 to 5.3 million women in the United States experience IPV. The large number of individuals affected, the enormous healthcare costs, and the need for a multidisciplinary approach make IPV an important healthcare issue. The Violence Against Women Act (VAWA) addresses domestic violence, dating violence, sexual assault, and stalking. It emphasizes development of coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 28 publications
0
72
0
1
Order By: Relevance
“…While it was found that in the United States many emergency departments, shelters, agencies, and clinics had IPV advocacy programs, most of these programs historically failed in responding adequately to abuse in LGB groups (Brown and Groscup, 2009; Hines and Douglas, 2011; Armstrong et al, 2014). Goodman et al (2015) contended that during initial steps, services providers should recognize the problem, offer empathic support, ensure safety, and help the victim gain distance from a dangerous situation.…”
Section: Lgb Ipv Assessment and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…While it was found that in the United States many emergency departments, shelters, agencies, and clinics had IPV advocacy programs, most of these programs historically failed in responding adequately to abuse in LGB groups (Brown and Groscup, 2009; Hines and Douglas, 2011; Armstrong et al, 2014). Goodman et al (2015) contended that during initial steps, services providers should recognize the problem, offer empathic support, ensure safety, and help the victim gain distance from a dangerous situation.…”
Section: Lgb Ipv Assessment and Treatmentmentioning
confidence: 99%
“…Goodman et al (2015) contended that during initial steps, services providers should recognize the problem, offer empathic support, ensure safety, and help the victim gain distance from a dangerous situation. Healthcare workers should screen for IPV in LGB patients and understand how patterns of IPV are different for these patients (Banks and Fedewa, 2012; Armstrong et al, 2014): standard approaches to IPV screening may be ineffectual for LGB people (Cavacuiti and Chan, 2008). Ard and Makadon (2011) highlighted the need for a sensitive and accurate assessment, which they discussed through clinical, institutional, educational, and research suggestions.…”
Section: Lgb Ipv Assessment and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be especially true in situations where resources and financial means are limited (e.g., 70.5% of women were foreign-born in the current study). Minority women may also be faced with additional challenges that prevent them from seeking help or leaving abusive partners, such as legal concerns, unemployment, cultural stigma, and linguistic barriers (Hazen and Soriano 2007;Magnussen et al 2007;Modi, Palmer, and Armstrong 2014;NajafiSharjabad et al 2013;Quelopana and Alcalde 2014;Stockman, Hayashi, and Campbell 2015). Interventions should consider the confluence of socio-economic, cultural, political, and religious factors that affect unintended pregnancy rates in women who stay or are trapped in abusive relationships.…”
Section: Discussionmentioning
confidence: 99%